2004
DOI: 10.1161/01.cir.0000138393.99310.1c
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection in Heart Transplant Recipients Is Associated With Impaired Endothelial Function

Abstract: Background-Cardiac allograft vasculopathy (CAV) is initiated by allograft endothelial injury. We hypothesized that a major mechanism by which cytomegalovirus (CMV) could contribute to CAV is by dysregulation of the endothelial vasomotor response. Methods-Coronary endothelial vasomotor function was determined in 183 consecutive patients (24Ϯ33 months after transplantation), and was correlated with recipient and donor CMV serological status before transplantation and with documented CMV infection episodes (CMVpp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 32 publications
1
64
0
Order By: Relevance
“…Human cytomegalovirus infection exerts an inhibitory effect on endothelial nitric oxide synthase activation, thereby reducing nitric oxide production, activating the stress-response signal P38-MAPK pathway, and upregulating phosphatase and tensin homolog, 21,22 leading to endothelial dysfunction. 23,24 Human cytomegalovirus infection stimulates renin and angiotensin II expression in human vascular endothelial cells, 39 enhancing NAD(P)H oxidase activity, and elicits the production of reactive oxygen species. Reactive oxygen species directly cause vasoconstriction through modulation of calcium levels and/or arachidonic acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human cytomegalovirus infection exerts an inhibitory effect on endothelial nitric oxide synthase activation, thereby reducing nitric oxide production, activating the stress-response signal P38-MAPK pathway, and upregulating phosphatase and tensin homolog, 21,22 leading to endothelial dysfunction. 23,24 Human cytomegalovirus infection stimulates renin and angiotensin II expression in human vascular endothelial cells, 39 enhancing NAD(P)H oxidase activity, and elicits the production of reactive oxygen species. Reactive oxygen species directly cause vasoconstriction through modulation of calcium levels and/or arachidonic acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…17 It has been implicated in several cardiovascular disorders, including atherosclerosis, coronary heart disease, and cardiac transplant arteriopathy. 18 -20 Some studies suggest an association between HCMV and cardiovascular disorders through impaired endothelial nitric oxide synthase function 21,22 and subsequent endothelial dysfunction, 23,24 resulting in reduced vascular dilation in vivo. However, direct links between HCMV infection, endothelial dysfunction, and essential hypertension remain undefined.…”
mentioning
confidence: 99%
“…CMV is implicated in vascular complications through endothelial dysfunction. In heart transplant patients, CMV infection episodes are associated with impaired coronary endothelial function (13). Moreover, Fearon et al (14) reported that CMV seropositivity and the lack of prophylaxis against CMV correlate with negative remodeling of coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…43 Epicardial and microvascular endothelium-dependent and -independent vasomotor dysfunction are frequently observed after HTx. 44 Coronary allograft endothelial dysfunction is associated with circulating endothelin levels, 45 enhanced graft cytokine activation, 46 and CMV infection, 47 whereas statin treatment reduces the progression of epicardial and microvascular dysfunction. 48 Coronary endothelial dysfunction predicts the development of intimal thickening 49 and predicts cardiovascular end points after HTx.…”
Section: Detection Of Coronary Vasomotor Alterationsmentioning
confidence: 99%